2017
DOI: 10.4082/kjfm.2017.38.4.213
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Parental Support in the Relationship between Life Stress and Suicidal Ideation among Middle School Students

Abstract: Background: Youth suicide is increasingly being recognized as a major social problem in South Korea. In this study, we aimed to explore the effects of parental support on the relationship between life stress and suicidal ideation among middle-school students. Methods: This study analyzed data from a cross-sectional study on mental health conducted by the South Korea National Youth Policy Institute between May and July of 2013. Questionnaire responses from 3,007 middle-school students regarding stress factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…We also found that parents of adolescent girls monitored their leisure activities more than parents of adolescent boys, whereas the differences for other aspects of the relationship did not vary widely between sexes. However, our results are not directly comparable to other studies looking at parental factors, particularly because each study measured various aspects of parental support and relationship using different definitions [ [11] , [12] , [13] , [14] , [15] , [16] , 18 , 23 , 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We also found that parents of adolescent girls monitored their leisure activities more than parents of adolescent boys, whereas the differences for other aspects of the relationship did not vary widely between sexes. However, our results are not directly comparable to other studies looking at parental factors, particularly because each study measured various aspects of parental support and relationship using different definitions [ [11] , [12] , [13] , [14] , [15] , [16] , 18 , 23 , 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The findings indicated that young adolescents are more likely to develop suicidal ideation if their parents give them excessive attention on a daily basis. These results corroborate the findings of previous studies in examining the role of parents on adolescents' suicidal behaviour (22)(23)(37)(38)(39). Such discovery supports the current literature, indicating that helicopter parenting could lead to various challenges among adolescent children.…”
Section: Discussionsupporting
confidence: 90%
“…According to Kawachi and Berkman (2001), "the perceived availability of functional support is thought to buffer the effects of stress by enhancing an individual's coping abilities." Kang et al (2017) further indicated that parental support particularly mediated the relationship between life stress and suicidal ideation among middle school students. Similarly, another previous study showed that greater levels of perceived family support were associated with a weaker the relationship between depression and suicidal ideation among adolescents (Rubio et al 2020).…”
Section: Discussionmentioning
confidence: 92%